Exploratory Analysis of Changes in Global Parameters Around Sightings of Unidentified Aerial Phenomena - Coleman, Les (Journal of Scientific Exploration, 2023)
Unidentified aerial phenomena (UAP) have long been associated with earthquakes and other geophysical occurrences and are seen by government agencies in the United States and elsewhere as possibly significant to national security. Despite that, the mechanisms driving UAP are unclear. This study contributes to their better understanding by looking at UAP as more than sighting reports and conducts an atheoretical, data-driven review that seeks to identify their statistical associations with global geophysical and anthropomorphic parameters. The analysis covers the period 1995-2020 and includes 19 variables with annual and monthly frequency. UAP sightings are from NUFORC and mainly cover North America, which encompasses 17 percent of Earth’s land area and is a sample of global data. Here we show that reports of UAP sightings are preceded by changes of the same sign in stock prices and of the opposite sign in airliner crashes, atmospheric carbon dioxide, and earthquakes. UAP sightings are then accompanied or followed by changes of the same sign in airliner crashes, battle deaths, earthquakes, global temperature, sunspots, and volcanic eruptions; and by changes of the opposite sign in atmospheric carbon dioxide, cosmic radiation, mental health deaths, natural disasters, and tropical storms. This analysis highlights a potentially important scientific gap whereby UAP is associated with diverse global parameters and provides a basis for further study.